Production-Based Asset Pricing and the Link Between Stock Returns and Economic Fluctuations. - Cochrane, John H (Journal of Finance, 1991)
This paper describes a production-based asset pricing model. It is analogous to the standard consumption-based model, but it uses producers and production functions in the place of consumers and utility functions. The model ties stock returns to investment returns (marginal rates of transformation), which are inferred from investment data via a production function. The production-based model is used to examine forecasts of stock returns by business-cycle related variables and the association of stock returns with subsequent economic activity.